2014
DOI: 10.18632/oncoscience.103
|View full text |Cite
|
Sign up to set email alerts
|

MDM4 expression as an indicator of TP53 reactivation by combined targeting of MDM2 and MDM4 in cancer cells without TP53 mutation

Abstract: MDM2 and MDM4, a structurally related MDM2 homolog, negatively regulates expression and functions of TP53 tumor suppressor gene. To explore the precise expression patterns and function of MDM2 and MDM4 in wild-type (wt) TP53 cancer cells, we analyzed 11 various cancer cell lines with wt TP53. All cell lines exhibited deregulated expression of MDM2 and MDM4, and were divided into two distinct types; the one expressing high levels of MDM4 and another expressing low levels of MDM4. The low MDM4 type expressed hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…In our previous study, simultaneous knockdown of MDM4 and MDM2 using synthetic DNA-substituted siRNAs (chiMDM4 and chiMDM2) was shown to synergistically suppress the growth of cancer cells with wtTP53/ highMDM4. 16 In this study, we showed that double knockdown of MDM4 and MDM2 enhanced the antitumor activity of 5-FU in colon and gastric cancer cells with wtTP53/highMDM4.…”
Section: -Fu Is Widely Used For Chemotherapy In Various Cancers Includ-mentioning
confidence: 62%
See 4 more Smart Citations
“…In our previous study, simultaneous knockdown of MDM4 and MDM2 using synthetic DNA-substituted siRNAs (chiMDM4 and chiMDM2) was shown to synergistically suppress the growth of cancer cells with wtTP53/ highMDM4. 16 In this study, we showed that double knockdown of MDM4 and MDM2 enhanced the antitumor activity of 5-FU in colon and gastric cancer cells with wtTP53/highMDM4.…”
Section: -Fu Is Widely Used For Chemotherapy In Various Cancers Includ-mentioning
confidence: 62%
“…A previous study reported that cultured tumor cells with wt TP53 can be divided into 2 types: high MDM2 expressers and high MDM4 expressers . The former expresses a high level of MDM2 and a very low level of MDM4, whereas the latter expresses a high level of MDM4 and an intermediate level of MDM2.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations